Performance and microbial analysis during long‐term anaerobic digestion of olive mill wastewater in a packed‐bed biofilm reactor. Issue 3 (15th December 2019) - Enaime, Ghizlane; Nettmann, Edith; Berzio, Stephan; Baçaoui, Abdelaziz; Yaacoubi, Abdelrani; Wichern, Marc; Gehring, Tito; Lübken, Manfred
Abstract: BACKGROUND: The treatment of olive mill wastewater (OMWW) in a packed bed biofilm reactor (PBBR) and the identification of different microorganisms involved in the digestion process is an attractive field for research. RESULTS: A PBBR treating OMWW under different organic loading rates (OLRs) (0.94–9.36 gCOD/(L d)), showed high stability during an extensive time (723 days) without any sign of acidification. High volumetric biogas and methane (CH4 ) productions, 4.1 and 2.4 LN /(Lreactor d), respectively were registered at the highest OLR. Meanwhile, high chemical oxygen demand (COD) removal (62.5–79.7%) was obtained throughout the experiment. Phenolic compounds removal was much higher during the first steps of the experiment (75.9–84.2%), and decreased as the OLR increased to about 38%. High homogeneity of biofilm thickness and Bacteria and extracellular polymeric substance distribution were demonstrated by confocal laser scanning microscopy. Results of real‐time quantitative polymerase chain reaction (PCR) and 16S rRNA amplicon analyses showed that Bacteria, mainly consisting of Firmicutes, Proteobacteria, Bacteroidetes and Chloroflexi phylum, was about eight times more abundant than Archaea in the reactor liquid phase, while Bacteria to Archaea ratio was almost one in the biofilm. This points to a major degradation of organic substances in the liquid, while methanogenesis occurred mainly within the biofilm. In the liquid, acetoclastic methanogens were more abundant than hydrogenotrophic ones, while both groups showed likely very similar contributions in the biofilm. CONCLUSION: Promising results have been presented throughout this work providing information about the long‐term operation of PBBR‐granular activated carbon treating OMWW and analyzing, in an efficient manner, the structure and the composition of the microbial community involved in OMWW digestion. © 2019 Society of Chemical Industry